Diffusion of food safety management system prerequisite programs among micro, small and medium food suppliers of selected hotels in Metro Manila, Philippines an exploratory research - Antigua, Bryan Lee A. (University of the Philippines Diliman, 2014)
This exploratory research aims to investigate the diffusion of food safety management system prerequisite programs among micro, small and medium food suppliers of selected hotels in Metro Manila, Philippines. Selected hotels' food safety requirements for their suppliers were analyzed and compared to the requirements of the local government and an international standard in order to assess the completeness and level difficulty of the hotels' food safety requirements. Diffusion curves of 17 food safety management system prerequisite programs were drawn using the result of a desk review of a total 428 supplier audit reports, which were conducted by the selected hotels from January 2008 to June 2012. Majority of food suppliers has adopted food safety system prerequisite programs related to stock rotation; monitoring storage temperature; warehousing; vehicles, conveyances and containers; storage of food, packaging materials and ingredients; lighting; waste disposal; product contact surfaces; cleaning and sanitizing agents and tools; personal cleanliness and behavior; and workwear and protective clothing. However, less adoption among food suppliers were observed in food safety system prerequisite programs related to water supply; pest control; preventive and corrective maintenance; cleaning plant, utensils and equipment; health status; personnel hygiene facilities and toilets; and food safety training. Barriers to the wider adoption of food safety management system prerequisite programs among MSME food suppliers that were identified in this study are lack of knowledge of selected hotels' requirements, lack of or inadequate financial resources, lack or management commitment, poor leadership or lack of technical expertise to drive the food safety management system implementation, and inadequate food safety training. Recommendations were made on future research to further investigate the diffusion of food safety system prerequisite programs among micro, small and medium food enterprises in the Philippines.